Evaluation of the Relationship Between Suspicion of Abuse/Neglect and Depression in Individuals Over 65 Years of Age: Self-Awareness Study - Turla, Ahmet; Kuloğlu, Muhammet Mustafa; Cankurt Ayar, Nilay (The Bulletin of Legal Medicine, 2024)
Objective: This study aims to evaluate abuse and neglect in the elderly, its relationship with depression, and insight in those suspected of abuse and neglect. Methods: The population of the study consisted of 307 elderly individuals who applied to the outpatient clinics of Ondokuz Mayis University Hospital, who could read, write and had no speech or comprehension problems. In addition to questions on sociodemographic characteristics; the Yesavage Geriatric Depression Scale, Elder Abuse Suspicion Index and a question about patients’ self-awareness of individual abuse-neglect were used as data collection tools. Results: The possibility of depression was higher in primary school graduates, those who lived with family members or caregivers, and those with chronic illness. Suspicion of abuse was higher in primary school graduates, those who lived with family members or caregivers, those who had no income of their own, those with chronic illness and those who were taking psychiatric medication. Among the cases with suspicion of abuse, 58.8% were of the opinion that they had not been abused (p<0.05 for each). When the relationship between cases with suspected abuse and suspected depression was analyzed, a statistically moderate positive correlation between them (r=0.529, p<0.001) was found. Conclusion: In our study, the low rate of cases with self-awareness and suspicion of abuse indicates the importance of informing the elderly about abuse and neglect, teaching which behaviours should be considered as abuse and neglect. The elderly who are aware of being abused and neglected will be more willing and courageous to seek help.